Characterization of micro-invasive trabecular bypass stents by ex vivo perfusion and computational flow modeling - Hunter KS (Dove Medical Press, 2014)
Kendall S Hunter,1 Todd Fjield,2 Hal Heitzmann,2 Robin Shandas,1 Malik Y Kahook3 1Department of Bioengineering, University of Colorado Denver, Aurora, CO, USA; 2Glaukos Corporation, Laguna Hills, CA, USA; 3University of Colorado Hospital Eye Center, Aurora, CO, USA Abstract: Micro-invasive glaucoma surgery with the Glaukos iStent® or iStent inject® (Glaukos Corporation, Laguna Hills, CA, USA) is intended to create a bypass through the trabecular meshwork to Schlemm's canal to improve aqueous outflow through the natural physiologic pathway. While the iStent devices have been evaluated in ex vivo anterior segment models, they have not previously been evaluated in whole eye perfusion models nor characterized by computational fluid dynamics. Intraocular pressure (IOP) reduction with the iStent was evaluated in an ex vivo whole human eye perfusion model. Numerical modeling, including computational fluid dynamics, was used to evaluate the flow through the stents over physiologically relevant boundary conditions. In the ex vivo model, a single iStent reduced IOP by 6.0 mmHg from baseline, and addition of a second iStent further lowered IOP by 2.9 mmHg, for a total IOP reduction of 8.9 mmHg. Computational modeling showed that simulated flow through the iStent or iStent inject is smooth and laminar at physiological flow rates. Each stent was computed to have a negligible flow resistance consistent with an expected significant decrease in IOP. The present perfusion results agree with prior clinical and laboratory studies to show that both iStent and iStent inject therapies are potentially titratable, providing clinicians with the opportunity to achieve lower target IOPs by implanting additional stents. Keywords: glaucoma, iStent, trabecular bypass, intraocular pressure, ab-interno, CFD